Possibilidades de ações empreendedoras na gestão pública municipal: o caso do Matadouro Municipal de Telêmaco Borba/PR - Rodrigues, Fábio Henrique (2012)
This study highlights the main aspects of public entrepreneurship, discusses the role of public organization, highlighting its importance and requirements. It analyzes the commercial possibilities of the destination of bovine carcasses as an entrepreneurial action It explains the origin of the term, followed by a brief history of its use, as well as their theories. In a second stage, raises the theoretical aspects of entrepreneurship highlighted in public administration. Seeks to understand the action taken in the public sector. To this end, shows the importance of checking how entrepreneurial activity occurs within the municipal public administration, through conceptual and qualitative analysis of the subject. Uses, then the case of the beef carcass at the Municipal Slaughterhouse of Telemaco Borba / PR. Ponder on the current situation and the suggested solution to the allocation given to the case of carcasses from the perspective of Entrepreneurship and Public Management.